Study of Risk Factors for Catheter-Associated Urinary Tract Infection - Hamida El Magrahi; Abir Ben Ashur; Mawada Ben Khalil; Maram Ben Taboun; Zeinab Bleha (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Catheter-associated urinary tract infections (CAUTIs) are the most common causes of UTIs in ICU cases. Many risk factors are associated with its incidence. This study aimed to determine related risk factors contributing to urinary tract infection and to identify contaminated bacteria species, as well as their susceptibility profiles to the most commonly used antimicrobial agents. Methods. The study was performed at the University of Tripoli from February to May 2022. 180 catheterized patients from different clinical wards in ICUs at University Teaching Hospital, Tripoli city Libya, were included in this research. Two urine samples were taken from all patients before and after catheterization. The samples were cultured according to the standard microbiological procedures. Isolates were identified by conventional identification methods. The questionnaire was submitted to all patients to collect information such as age, gender, and health condition. Results. The age of the patients varied from a minimum of 15 years to a maximum of 73 years with a mean age of 37.82 years. Among them 96(53.33%) were males and 84(46.67%) were female patients. Out of 180 catheterized patients, only 93(51.67%) patients showed significant growth. On multivariate analysis, age, sex, duration of catheterization, and diabetes, were found to be the significant risk factors associated with CAUTI (p<0.05). All the urine cultures were monomicrobial. Gram-negative isolated species 69(74.19%), and Gram-positive isolated species 24(25.81%) Most common organism grown in culture was Escherichia coli 27 (29.03%) followed by Klebsiella pneumoniae 18 (19.36%), Pseudomonas aeruginosa 12 (12.90%), Enterococcus fecalis 12 (12.90 %), Staphylococcus aureus 9(9.67%), Enterobacter spp 6(6.45%), and Citraobacter spp, Acinetobacter spp, Streptococcus spp 3(3.23). Conclusion. An understanding of the risk factors in the development of CAUTI, significantly helps in reducing the additional burden on the health care system.